Notre-Dame de Paris as a validation case to improve fire safety modelling in historic buildings - Guibaud, Augustin; Mindeguia, Jean-Christophe; Albuerne, Alejandra; Parent, Thomas; Torero, José Luis (Elsevier, 2023)
The analysis of the thermal damages in Notre-Dame de Paris is necessary to estimate the impact of the dramatic 2019 fire on the remaining structure prior to reconstruction. In doing so, the large amount of data being generated creates a benchmark environment to test the relevance of numerical fire models in the unconventional configuration of a medieval roof. While being an uncontrolled and complex configuration, it can provide insights regarding the relevance of numerical tools for fire risk assessment in historic buildings. Analysing the thermal degradation of the Lutetian limestone in a vault of the choir, experimental techniques are developed to track the in-depth maximum temperature profile reached during the fire. Numerical simulations of the fire development in the roof space then aim at replicating the observations through the evaluation of the heat flux impinging the vaults during the fire. These simulations are carried out using Fire Dynamic Simulator, which requires a large range of assumptions prior to any simulation regarding materials, geometry, meshing and scale. These assumptions are described and pave the way to a future sensitivity analysis to confront the upcoming outcomes of the simulations with the experimental observations.
Keywords: 33 Ciencias Tecnológicas::3305 Tecnología de la construcción ::3305.32 Ingeniería de estructuras; ODS 11 - Ciudades y comunidades sostenibles; Notre-Dame de Paris; Fire; Simulation; Masonry; Limestone; Temperature